Gambar Dalam Proses Pembelajaran Pendidikan Agama Hindu Di Sd Negeri 2 Dauh Peken Tabanan - I Gusti Ayu Kade Indri Sari; I Wayan Mandra; Ida Ayu Adi Armini (Jurnal Penelitian Agama Hindu, 2019)
Image media is the result of hand painting that is printed or produced or the results of photography are poured in the form of images that have maximum appeal. In SD Negeri 2 Dauh Peken Tabanan in the process of learning Hindu education, the teacher tried to use picture media as a teaching aid because of the lack of student interest in Hindu religious education. The theory used to analyze problems is: Behavioristic Theory and motivation theory. This research approach is qualitative from primary data obtained through field research and secondary data obtained from several library documentation. To obtain data about the application of image media researchers applied data collection methods with methods of observation, interviews, literature and documentation. The collected data were analyzed using qualitative descriptive techniques with steps of reduction, data presentation, and conclusion drawing. The results of this study are (1) The application of image media in the learning process in this study took 4 stages, namely preparation, presentation, follow-up and closing. (2) Obstacles in the application of image media are indogeneous factors and exogeneous factors. (3) Efforts made in the application of image media are maximizing the making of image media, good classroom management and internal teacher and school policies.